SYNTHESIS, MOLECULAR AND CRYSTAL STRUCTURE, AND BIOLOGICAL ACTIVITY OF A NEW METAL COMPLEX DERIVED FROM 4-AMINOBENZOIC ACID - A.R. Safarov; I.A. Karimov; A.N. Serobov; B.A. Atajanov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. A novel zinc(II) complex derived from 4-aminobenzoic acid (PABA) was synthesized using ZnCl₂ as the metal precursor. The complex was characterized by elemental analysis, FTIR, UV–Vis, NMR, thermal gravimetric analysis (TGA), and single-crystal X-ray diffraction (SCXRD). Spectral and structural data confirmed the bidentate coordination of the ligand through the carboxylate oxygen and amino nitrogen atoms, forming a distorted octahedral geometry around the Zn(II) center. The crystal packing was stabilized by an extensive network of intermolecular hydrogen bonds and π–π stacking interactions. The thermal analysis revealed high stability of the complex up to 300 °C, while biological screening demonstrated significant antibacterial and antioxidant activity compared to the free ligand. The results suggest that the synthesized Zn(II) complex can serve as a promising multifunctional compound for bioinorganic and pharmaceutical applications.